Acute kidney injury caused by tenofovir disoproxil fumarate and diclofenac co‐administration. Issue 10 (28th August 2013) - Bickel, M; Khaykin, P; Stephan, C; Schmidt, K; Buettner, M; Amann, K; Lutz, T; Gute, P; Haberl, A; Geiger, H; Brodt, HR; Jung, O
<x xml:space="preserve">Abstract</x> Objectives The renal elimination of tenofovir (TFV) may be subject to renal drug−drug interactions that may increase the risk of kidney injury. Case reports indicated that diclofenac might increase TFV‐associated nephrotoxicity via a drug−drug interaction, leading to an increased intracellular TFV concentration in proximal tubular cells. Methods A retrospective analysis of data for all patients from the Frankfurt HIV Cohort (FHC) who had diclofenac prescriptions between January 2008 and June 2012 was carried out. Results Among 89 patients with diclofenac use, 61 patients (68.5%) were treated with tenofovir disoproxil fumarate (TDF) and 28 patients (31.5%) were treated with TDF‐sparing combination antiretroviral therapy (cART). Thirteen patients (14.6%) developed acute kidney injury (AKI) shortly after initiating diclofenac treatment. AKI occurred exclusively in TDF‐treated patients, although all had previously stable renal function. All cases were accompanied by new onset of at least two parameters indicating proximal tubular damage, such as normoglycaemic‐glucosuria and hypophosphataemia. TFV‐associated nephrotoxicity was demonstrated by renal biopsy in four cases. Additionally, 11.5% of patients on TDF treatment developed new‐onset proximal tubular damage, while having a preserved glomerular filtration rate. In contrast, diclofenac did not affect renal function in patients with TDF‐sparing cART, as only one case of isolated hypophataemia was observed in these patients. In univariate analysis, risk factors for AKI were TDF‐containing cART (P = 0.0076) and pre‐existing hypophosphataemia (P = 0.0086). Conclusions Drug−drug interaction caused by diclofenac could exacerbate TFV‐associated nephrotoxicity. Diclofenac should be used with caution in patients on TDF therapy, especially in those with hypophosphataemia. Our findings need to be confirmed in larger studies.